"Buy, wear, return, repeat": Investigating Chinese consumers' attitude and intentions to engage in wardrobing. (5th May 2022) - Phau, Ian; Akintimehin, Olamide Oluwabusola; Shen, Bin; Cheah, Isaac
Abstract: Social factors are the major antecedents to attitude and intention to engage in wardrobing among Chinese luxury‐fashion consumers within an e‐commerce context. Fraudulent product returns (wardrobing) are most common within the e‐commerce retail luxury‐fashion sector. Western retail luxury‐fashion consumers attribute their attitude and wardrobing intentions to various personality and social factors, while the motivations of Chinese consumers to engage in wardrobing is mainly linked to key social factors like experience and knowledge of return policy. From a practical and managerial perspective, the fundamental role of cultural differences emerging from our findings compared to previous studies offers retail executives a greater understanding of product return strategy.